The relationship between the service quality dimension and the customer satisfaction at MITC Melaka / Nurul Athirah Zabidi - Zabidi, Nurul Athirah (2014)
The focus of this study is “The Relationship between Service Quality and Customer Satisfaction in MITC, Melaka”. The factors that we are highlight in this research were service quality dimensions that can be the guidelines in improving the customer satisfaction. The research objective is to investigate the relationships between reliability as service quality dimensions with the customer satisfaction, the relationships between reliability as service quality dimensions with the customer satisfaction, the relationships between responsiveness as service quality dimensions with the customer satisfaction, the relationships between assurance as service quality dimensions with the customer satisfaction, the relationships between empathy as service quality dimensions with the customer satisfaction, the relationships between tangible as service quality dimensions with the customer satisfaction and to provide the recommendation to the company. The study utilized questionnaire as the instrument for collecting data. Questionnaires had been distributed to 100 customers or clients that have function at the organization to do the research. The researchers will have used the Statistical Package for Social Science (SPSS) version 20. From the analysis, the researchers have identified that there is significant relationship between service quality and customer satisfaction in MITC, Melaka. It means that the stronger the strength of the relationship the accurate and reliable the result the company can maintain the dimensions and improve weak relationship. The results indicated that overall customers were satisfied by the service quality but there are some areas that need to be improved and make some adjustments. Several recommendations were suggested to help MITC give better service quality.